2016
DOI: 10.1093/nar/gkw1150
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transcription initiation directed by multiplecis-regulatory elements on theglnAp2promoter

Abstract: Transcription initiation is orchestrated by dynamic molecular interactions, with kinetic steps difficult to detect. Utilizing a hybrid method, we aim to unravel essential kinetic steps of transcriptional regulation on the glnAp2 promoter, whose regulatory region includes two enhancers (sites I and II) and three low-affinity sequences (sites III-V), to which the transcriptional activator NtrC binds. By structure reconstruction, we analyze all possible organization architectures of the transcription apparatus (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…Upstream of the glnAp2 promoter, there are two enhancer sequences and three low-affinity sequences for the binding of transcriptional activator nitrogen regulatory protein C (NtrC). In contrast with the traditional view that transcription initiation is stimulated by an NtrC hexamer simultaneously bound to the two enhancers, Wang et al (2016) revealed that the initiation is stimulated by an NtrC hexamer at either enhancer ( Fig. 3).…”
Section: Transcriptional Bursting In Bacteriacontrasting
confidence: 76%
See 3 more Smart Citations
“…Upstream of the glnAp2 promoter, there are two enhancer sequences and three low-affinity sequences for the binding of transcriptional activator nitrogen regulatory protein C (NtrC). In contrast with the traditional view that transcription initiation is stimulated by an NtrC hexamer simultaneously bound to the two enhancers, Wang et al (2016) revealed that the initiation is stimulated by an NtrC hexamer at either enhancer ( Fig. 3).…”
Section: Transcriptional Bursting In Bacteriacontrasting
confidence: 76%
“…Investigating transcriptional dynamics necessitates both live imaging methods with high resolution (Skupsky et al ., ; Suter et al ., ; Evans et al ., ; Friedman, Mumm, & Gelles, ; Gebhardt et al ., ; Hocine et al ., ; Kouno et al ., ; Lickwar, Mueller, & Lieb, ; Yunger et al ., ; Sidaway‐Lee et al ., ; Annibale & Gratton, ; Camunas‐Soler et al ., ; Gocheva et al ., ; Roberts et al ., ; Rybakova et al ., ; Corrigan et al ., ; Tantale et al ., ) and quantitative computer simulations with appropriate theories and models (Skupsky et al ., ; Suter et al ., ; Wang et al ., ; Maina et al ., ; Choubey, Kondev, & Sanchez, ; Stefan et al ., ; Rybakova et al ., , b ; Corrigan et al ., ; Tantale et al ., ). Specifically, integrating diverse sets of data makes it possible to present a coherent dynamic picture of gene transcription in bacteria (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar patterns of strong activation and weak repression sites have also been observed in other autoregulated TCS promoters, such as phoBR in Vibrio cholerae ( Diniz et al, 2011 ) and glnALG in E. coli ( Atkinson et al, 2002 ). Although the mechanism of transcription repression appears to be different as suggested by different positions of repression sites ( Diniz et al, 2011 ; Wang et al, 2016 ), weak repression sites function to similarly limit the maximal concentration at high TF levels. Dual autoregulatory TFs constitute a non-trivial fraction (~10%) of autoregulated TFs in E. coli ( Martínez-Antonio et al, 2008 ), and this number may even be underestimated due to difficulties in uncovering the weak autoregulatory interactions.…”
Section: Discussionmentioning
confidence: 99%